(untitled) (Kathmandu University Medical Journal, 2014)
Background The endocrine changes related to altitude adaptation in human have attracted physiologists around the globe for long. A number of high altitude studies to detect the physiological changes have been performed now and then. But, the study to see the hormonal changes to compare populations residing at different high altitudes is a scarce. Hence, we have performed a study in native populations of different high altitude comparing changes in thyroid hormones in western Nepal. The Jharkot population included in this study is at altitude of 3760m and Jomsom population at 2800m height from sea bed. Objective The study is to compare changes in thyroid hormones at two different high altitude natives. Methods To compare thyroid status between high altitude natives at two different altitudes a cross sectional study is performed by random sampling method. The blood sample was collected in a vacutainer from fifty eight individuals after obtaining the informed consent of participants. The blood collected from antecubital vein was centrifuged in an hour and the serum obtained was used for biochemical analysis of free triiodothyronine, free thyroxine and thyroid stimulating hormone. Results Mean free thyroxine (fT4) of Jharkot population is significantly larger (p = 0.001) than Jomsom population. Mean thyroid stimulating hormone (TSH) with p = 0.597, does not indicate the difference between this two population. There is no significant difference between mean free triiodothyronine (fT3) of Jharkot and Jomsom population (p = 0.345). Conclusion The rise in free thyroid hormone at high altitude is not dependent on the thyroid stimulating hormone released from anterior pituitary. The rise in free thyroxine is found at higher altitude and no difference in fT3 level is detected in population studied at high altitudes. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11017 Kathmandu University Medical Journal Vol.11(1) 2013: 18-21